2021
DOI: 10.3389/fped.2021.713516
|View full text |Cite
|
Sign up to set email alerts
|

Nasotracheal vs. Orotracheal Intubation and Post-extubation Airway Obstruction in Critically Ill Children: An Open-Label Randomized Controlled Trial

Abstract: Background: The data on long-term nasotracheal intubation among mechanically ventilated critically ill children is limited. The purpose of this study was to compare the rate of post-extubation airway obstruction (PEAO) with nasotracheal and orotracheal intubation.Methods: This open-label randomized controlled trial was conducted in PICU of a tertiary care and teaching hospital in North India from January-December 2020 involving intubated children aged 3 months−12 years. After written informed consent, children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…However, it was worth noting that anesthesia time, insufflation time, and removal time showed similar results across the studied groups. In consistency with the current study Ahn et al (6) revealed that in comparison with the ETT group, the median insertion time was lower in the Baska group (21.0 s, P=0.000) than in the latter (27.0 [24][25][26][27][28][29][30][31][32][33] s. Also, Maged et al (30) reported that the device insertion time was greatly reduced by the Baska group (28.4±10.7 vs 46.6±19.8, P=0.001).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it was worth noting that anesthesia time, insufflation time, and removal time showed similar results across the studied groups. In consistency with the current study Ahn et al (6) revealed that in comparison with the ETT group, the median insertion time was lower in the Baska group (21.0 s, P=0.000) than in the latter (27.0 [24][25][26][27][28][29][30][31][32][33] s. Also, Maged et al (30) reported that the device insertion time was greatly reduced by the Baska group (28.4±10.7 vs 46.6±19.8, P=0.001).…”
Section: Discussionsupporting
confidence: 90%
“…Also, Abdel-Ghaffar et al (8) revealed that the median leak pressure in the BASKA group was 32.0 (29-35) cmH 2 O at the time of insertion. This value was reduced during pneumoperitoneum expansion (31.0 [27][28][29][30][31][32][33] cmH 2 O, P=0.000), and thereafter remained constant at this level (30.0 [27][28][29][30][31][32] cmH2O, P=0.000). Furthermore, Choi et al (28) revealed that throughout the procedure, the Baska mask maintained a steady oropharyngeal leak pressure of ≥ 33 cmH 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…A large database study of nasal intubation practices among pediatric cardiac surgery programs revealed that there is not an increased risk of infectious complications in neonates and infants, although older children and adolescents have the same risk pro le as adults (4). Our data supports the growing body of literature showing safety of nasal intubation in this population: our nasally intubated neonates did not experience mediastinitis, ventilator-associated pneumonia, or bacteremia (15). Pressure ulcer formation is a serious concern with nasal endotracheal tubes and should be monitored for diligently, though was infrequent in our sample (16).…”
Section: Discussionsupporting
confidence: 79%
“…Of note, two small randomized trials comparing nasal versus oral intubation in infants and young children exposed to brief courses of mechanical ventilation did not find a significant difference in skin injury between ETT locations. 5,6 The placement and management of nasal ETTs may also…”
Section: Discussionmentioning
confidence: 99%